Traumatic Brain Injury Pathobiology, Advanced Diagnostics and Acute Management - Gorbunov, Nikolai V.; Long, Joseph B. (IntechOpen, 2018)
Traumatic brain injury (TBI) syndrome has emerged as a serious health concern worldwide due to the severity of outcomes and growing socioeconomic impacts of the diseases, e.g., high cost of long-term medical care and loss of quality of life. This book focuses on the TBI pathobiology as well as on the recent developments in advanced diagnostics and acute management. The presented topics encompass personal experience and visions of the chapter contributors as well as an extensive analysis of the TBI literature. The book is addressed to a broad audience of readers from students to practicing clinicians.